Improved turbulence and transition closures for separated flows - Hodara, J.; Smith,M.J. (My University, 2015)
A new turbulence approach is proposed that combines the strengths of Unsteady Reynolds-Averaged Navier-Stokes (URANS) and Large Eddy Simulation (LES) turbulence closure with local dynamic kinetic model (LDKM) and the widely adopted g ??Reqt transition model. This method has the potential for accurately capturing massively separated boundary layers in the transitional Reynolds number range at a reasonable computational cost, and therefore holds great promise for the rotorcraft industry. Comparisons are evaluated on several cases, including a transitional flat plate, circular cylinder in crossflow and NACA 63-415 wing. Cost and accuracy correlations with URANS and prior hybrid URANS-LES approaches with and without transition modeling indicate that this new method can capture both separation and transition more accurately and cost effectively.
Keywords: Aerodynamics